Development of Smart Crop Monitoring System Using IoT - A. Vhaishnavi, Brunda M, Jasmin James, Joanita VJ, Prof. Rashmi Priyadarshini B K (International Journal of Advanced Science and Technology, 2020)
India is an agricultural country. 50 percent of Indian workforce is employed in agriculture and it contributes 17 to 18 percent to the GDP. Issues concerning agriculture can be addressed by detecting disease at an early stage. Health of the crop is monitored using Raspberry pi 3 B+, Pi camera module, Ultrasonic sensor, Soil moisture sensor, Temperature- humidity sensor and float switch. The sensors are connected and the images are captured using pi camera. Image is processed in Raspberry pi 3 B+ using image processing on MATLAB with pre-installed libraries for disease detection. As per the color, edges, background and pixel distance, the images are segmented. These segments will decide the diseases of the crop. Results of the same along with the solutions are informed to remote farmers using IoT technology. This digitized smart farming results in less wastage of crops and promotes agricultural efficiency.